Liturgical wooden carved cross from the collection of the Russian Icon Museum - Elena V. Guvakova (Российский журнал истории Церкви, 2020)
The paper considers a carved priestly cross of the XIX century from the representative collection of Ethiopian art of the Russian Icon Museum. This is one of the typical Ethiopian crosses with a characteristic rhomboid shape, with the image on the front side of the liturgical procession and the icon of the Mother of God, and ornamented on the back with a braided pattern with cross-shaped ornaments woven into it. The image of the dancing participants of the liturgical procession with drums and sistra represents a unique fusion of different traditions, the influence of the Old Testament tradition was manifested in the symbolic image of tabot.